A geografia econômica das sementes: dos grandes monopólios ao sudoeste do Paraná - Bandeira, João Luciano (2015)
The present work is a study of conjuncture of seeds in marketing worldwide, national and regional (southwestern of Paraná). Outlining the conjuncture of multiple determinations of seeds supplies are.., Strategy of conglomerates, monopolization of knowledge and imperialist of actions through the financial resources. The work is organized into three chapters, which are also marks its three keys points: 1) The delay in the development of sectors in Brazil in the countrie s headquarters of large corporations with rapid endogenous development and EMBRAPA becoming world reference in the production of improved seeds. The impacts of denationalization and its consequences. 2) chronic dependence of Agriculture in Brazilians studies input, this has being a consequences of the changes in form of technical assistance and rural extensionl added the pattern of financial changes. Events added to the weakening of IPPs in the 1990s and changes in legislation. The work shows the increasing vertiginous steep rise in the seeds sectors, noting the imperialist mechanism wealth of drainage in various agricultural areas of the world. 3) Brief history of the seed sector in Paraná Southwest. Changes in the amount and profile of local businesses with significant changes in recent decades and its relationship with multinationals.